Probing endogenous collagen by laser‐induced autofluorescence in burn wound biopsies: A pilot study. Issue 9 (16th May 2018) - Prabhu, Vijendra; Acharya, Anusha; Satish Rao, Bola S.; Rathnakar, Bharath; Kumar, Pramod; Guddattu, Vasudeva; Mahato, Krishna K.
Abstract : The focus of the current study was to interrogate the predictive potential of laser‐induced autofluorescence (LIAF) by objectively assessing collagen synthesis in burn wound granulation tissues ex vivo . Prior grafting, granulation tissues (20 samples) following burn injury were collected from 17 subjects of age range 18 to 60 years with patient/donor consent and the corresponding autofluorescence spectra were recorded at 325 nm He‐Cd laser (≈2 mW) excitations. The resulting endogenous collagen intensity from the above tissue samples was computed by normalizing the nicotinamide adenine dinucleotide levels. In addition, the hydroxyproline content was also estimated biochemically from the same granulation tissues. A comparative assessment of both LIAF and biochemical estimations for endogenous collagen by hydroxyproline resulted in strong positive correlation among them. The above relevant observations suggest that LIAF is equally informative as that of biochemical estimations, in evaluating endogenous collagen content in wound granulation tissues. Thus, it can be concluded that LIAF has the predictive potential, as a noninvasive objective tool to measure the endogenous collagen levels in wound biopsy tissues and provide complementary data conducive for making clinical decisions. Abstract : Timely, objective and independent assessment of collagen has a significant impact on the successful management of burn wounds. Changes in collagen in burn wound granulation tissues have been investigated ex vivo using laser‐induced autofluorescence and compared with biochemical measurements. This autofluorescence approach is quick, reliable, stain‐free and reproducible for probing endogenous fluorophores and useful in monitoring of tissue repair in clinical settings.